2009
DOI: 10.1007/s00339-009-5456-z
|View full text |Cite
|
Sign up to set email alerts
|

Micro-focussed XAFS spectroscopy to study Ni-bearing precipitates in the metal of corroded Zircaloy-2

Abstract: The present work concerns an investigation of the local atomic environment of Ni-containing secondary phase precipitates (SPP) present in the metal-part of Zircaloy-2 cladding tubes. An unirradiated Zircaloy-2 and two specimens irradiated in a commercial nuclear power plant are characterized using μ-focussed synchrotron radiation, and by x-ray absorption fine structure (XAFS) spectroscopy. The patterns of Ni K-edge XANES and EXAFS of SPP in unirradiated and irradiated cladding are found different. Considering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Interestingly, vacancy migration in the Zr 2 Ni system was determined to be anisotropic with a preference in the [001] direction [57], which will of course have a profound effect on point defect interactions and larger, extended defects and their evolution, especially in regard to SPP clusters containing both Fe-Cr and Fe-Ni regions. The Fe-Ni system does indeed become defective under neutron irradiation, as Kuri et al have demonstrated by comparing the EXAFS and XANES with and without neutron irradiation in a BWR [62]. The degree of disorder is, however, difficult to discern and although Kuri et al described a lack in postirradiation long-range order, the spectra show signs of local order that may exceed that of an amorphous system.…”
Section: Spp Dissolution and Amorphisationmentioning
confidence: 96%
“…Interestingly, vacancy migration in the Zr 2 Ni system was determined to be anisotropic with a preference in the [001] direction [57], which will of course have a profound effect on point defect interactions and larger, extended defects and their evolution, especially in regard to SPP clusters containing both Fe-Cr and Fe-Ni regions. The Fe-Ni system does indeed become defective under neutron irradiation, as Kuri et al have demonstrated by comparing the EXAFS and XANES with and without neutron irradiation in a BWR [62]. The degree of disorder is, however, difficult to discern and although Kuri et al described a lack in postirradiation long-range order, the spectra show signs of local order that may exceed that of an amorphous system.…”
Section: Spp Dissolution and Amorphisationmentioning
confidence: 96%